Efficacy of Combining Aggressive Hydration With Rectal Indomethacin in Preventing Post-ERCP Pancreatitis: A Systematic Review and Network Meta-Analysis. Issue 3 (25th March 2022) - Radadiya, Dhruvil; Brahmbhatt, Bhaumik; Reddy, Chakradhar; Devani, Kalpit
Abstract : Postendoscopic retrograde cholangiopancreatography pancreatitis (PEP) is the most common complication of endoscopic retrograde cholangiopancreatography pancreatitis (ERCP). No randomized controlled trial (RCT) has compared the efficacy of the American Society of Gastrointestinal Endoscopy and European Society of Gastrointestinal Endoscopy recommended interventions for PEP prevention. We assessed the effectiveness of these interventions using network meta-analysis. PubMed, EMBASE, and Cochrane databases were searched to identify RCTs investigating guideline-recommended interventions and their combinations [rectal nonsteroidal anti-inflammatory drugs (NSAIDs): indomethacin or diclofenac, pancreatic stent (PS), aggressive hydration (AH), sublingual nitrate) for PEP prevention. We performed direct and Bayesian network meta-analysis, and the surface under the cumulative ranking curve to rank interventions. Subgroup network meta-analysis for high-risk populations was also performed. We identified a total of 38 RCTs with 10 different interventions. Each intervention was protective against PEP on direct and network meta-analysis compared with controls. Except AH+diclofenac and NSAIDs+ sublingual nitrate, AH+indomethacin was associated with a significant reduction in risk of PEP compared with PS [odds ratio (OR), 0.09; credible interval (CrI), 0.003-0.71], indomethcin+PS (OR, 0.09; CrI, 0.003-0.85), diclofenac (OR, 0.09; CrI, 0.003-0.65), AH (OR, 0.09; CrI, 0.003-0.65), sublingual nitrate (OR, 0.07; CrI, 0.002-0.63), and indomethacin (OR, 0.06; CrI, 0.002-0.43). AH with either rectal NSAIDs or sublingual nitrate had similar efficacy. AH+indomethacin was the best intervention for preventing PEP with 95.3% probability of being ranked first. For high-risk patients, although the efficacy of PS and indomethacin were comparable, PS had an 80.8% probability of being ranked first. AH+indomethacin seems the best intervention for preventing PEP. For high-risk patients, PS seems the most effective strategy. The potential of combination of interventions need to be explored further.